Penelusuran Miskonsepsi Operasi Bilangan Bulat dalam Pembelajaran Matematika Pada Mahasiswa PGMI dengan Menggunakan Cri (Certainty of Respon Index) - Fatmahanik, Ulum (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2018)
Abstract: The academic anxiety in this paper is the misconception of MI prospective teachers at IAIN Ponorogo in understanding the concept of integer operations. This study aims to trace the misconception of integer operations which includes addition, subtraction, multiplication and division by using a number line. The research method used is descriptive qualitative. The subjects of this study are students of GMI.D class of PGMI IAIN Ponorogo who are taking the course of mathematics learning MI which amounted to 32 students. To trace the misconception of students used Certainty of Response Index (CRI) so as to distinguish between students who have misconception with students who do not understand the concept. The instrument used in this study is a test in the form of a diagnostic test in the form of essays accompanied by Certainty of Response Index (CRI), and interviews conducted on students who experience misconception. Based on the results of the search for misconceptions of integer operations the causes of such misconceptions are 1) the principle of using the number lines in inconsistent integer operations; 2) count operation and type of number; 3) the interpretation of the form a + (-b); a - (-b); a x b and a: b, 4) the number of irrelevant reference books; 5) wrong concept of integer operation.Â ÙÙØ®Øµ: Ø§ÙÙØ´ÙÙØ© Ø§ÙØ¯Ø§ÙØ¹Ø© ÙØ¥Ø¬Ø±Ø§Ø¡ ÙØ°Ù Ø§ÙØ¯Ø±Ø§Ø³Ø© ÙÙ Ø§ÙÙÙØ§ÙÙÙ Ø§ÙØ®Ø§Ø·Ø¦Ø© ÙØ¯Ù Ø·ÙØ§Ø¨ ÙØ³Ù Ø§ÙØªØ±Ø¨ÙØ© ÙØ¥Ø¹Ø¯Ø§Ø¯ ÙØ¯Ø±Ø³Ù Ø§ÙÙØ¯Ø§Ø±Ø³ Ø§ÙØ§Ø¨ØªØ¯Ø§Ø¦ÙØ© Ø§ÙØ¬Ø§ÙØ¹Ø© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø§ÙØÙÙÙÙØ© ÙÙÙÙØ±ÙØºÙ ÙÙ ÙÙÙ ÙÙÙÙÙ Ø¹ÙÙÙØ© Ø¹Ø¯Ø¯ ØµØÙØ. ÙØ¯Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø¥ÙÙ Ø§ÙØ¹Ø«ÙØ± Ø¹ÙÙ Ø§ÙÙÙØ§ÙÙÙ Ø§ÙØ®Ø§Ø·Ø¦Ø© Ø¹Ù Ø¹ÙÙÙØ© Ø¹Ø¯Ø¯ ØµØÙØ Ø§ÙÙØØªÙÙØ© Ø¹ÙÙ Ø§ÙØ¬ÙØ¹Ø ÙØ§ÙØ·Ø±ØØ ÙØ§ÙØªÙØ³ÙÙ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù Ø§ÙØ®Ø· Ø§ÙØ¹Ø¯Ø¯Ù. Ø§Ø³ØªØ®Ø¯Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« Ø·Ø±ÙÙØ© Ø§ÙØ¨ØØ« Ø§ÙÙØµÙÙ Ø§ÙÙÙÙÙ. ÙÙÙØ¶ÙØ¹Ø§Øª Ø§ÙØ¨ØØ« ÙÙ Ø·ÙØ§Ø¨Â  Ø§ÙØµÙ Â GMI.DÂ  Â ÙØ³Ù Ø¥Ø¹Ø¯Ø§Ø¯ ÙØ¹ÙÙÙ Ø§ÙÙØ¯Ø§Ø±Ø³ Ø§ÙØ¥Ø¨ØªØ¯Ø§Ø¦ÙØ© Ø§ÙØ¬Ø§ÙØ¹Ø© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø§ÙØÙÙÙÙØ© ÙÙÙÙØ±ÙØºÙ ÙÙÙ ÙØ¯Ø±Ø³ÙÙ ØªØ¹ÙÙÙ Ø§ÙØ±ÙØ§Ø¶ÙØ§Øª ÙÙÙØ¯Ø§Ø±Ø³ Ø§ÙØ¥Ø¨ØªØ¯Ø§Ø¦ÙØ©Ø ÙØ¹Ø¯Ø¯ÙÙ 32 Ø·Ø§ÙØ¨Ø§. ÙÙÙØ¹Ø«ÙØ± Ø¹ÙÙ Ø§ÙÙÙØ§ÙÙÙ Ø§ÙØ®Ø§Ø·Ø¦Ø© ÙØ¯Ù Ø§ÙØ·ÙØ§Ø¨ Ø§Ø³ØªØ®Ø¯ÙØª Ø£Ø¯Ø§Ø© Certainty of Response Index (CRI) ØØªÙ ÙÙÙÙ Ø§ÙØªÙØ±ÙÙ Ø¨ÙÙ Ø§ÙØ·ÙØ§Ø¨ Ø§ÙÙØµØ§Ø¨ÙÙ Ø¨Ø§ÙÙÙØ§ÙÙÙ Ø§ÙØ®Ø§Ø·Ø¦Ø© ÙØ§ÙØ·ÙØ§Ø¨ ØºÙØ± Ø§ÙÙØ§ÙÙÙÙ ÙÙÙÙØ§ÙÙÙ. ÙØ£Ø¯Ø§Ø© Ø§ÙØ¨ØØ« Ø§ÙÙØ³ØªØ®Ø¯ÙØ© ÙÙ Ø§ÙØ§Ø®ØªØ¨Ø§Ø± Ø§ÙØªØ´Ø®ÙØµÙ ÙÙÙÙ Ø§ÙØ£Ø³Ø¦ÙØ© Ø§ÙØ§Ø³ØªÙØ¹Ø§Ø¨ÙØ© ÙÙØ¹ÙØ§ Certainty of Response Index (CRI)Ø ÙØ§ÙÙÙØ§Ø¨ÙØ© Ø§ÙØªÙ ØªØ¬Ø±Ù Ø¹ÙÙ Ø§ÙØ·ÙØ§Ø¨ Ø§ÙÙØµØ§Ø¨ÙÙ Ø¨Ø§ÙÙÙØ§ÙÙÙ Ø§ÙØ®Ø§Ø·Ø¦Ø©. ÙÙØªØ§Ø¦Ø¬ Ø§ÙØ¨ØØ« Ø¯ÙØª Ø¹ÙÙ Ø£Ù Ø£Ø³Ø¨Ø§Ø¨ ÙÙÙØ¹ Ø§ÙÙÙØ§ÙÙÙ Ø§ÙØ®Ø§Ø·Ø¦Ø© ÙØ¯Ù Ø§ÙØ·ÙØ§Ø¨ ÙÙ : 1) Ø£Ø³Ø§Ø³ Ø§Ø³ØªØ®Ø¯Ø§Ù Ø§ÙØ®Ø· Ø§ÙØ¹Ø¯Ø¯Ù ÙÙ Ø¹ÙÙÙØ© Ø¹Ø¯Ø¯ ØµØÙØ Ø§ÙØºÙØ± Ø§ÙÙÙØ¶Ø¨Ø·Ø 2) Ø¹ÙÙÙØ© Ø§ÙØØ³Ø§Ø¨ ÙØ£ÙÙØ§Ø¹ Ø§ÙØ¹Ø¯Ø¯Ø 3) ØªÙØ³ÙØ± Ø§ÙØ´ÙÙ a + (-b);Â  a â (-b);Â  a x b dan a : b, Ø 4) ÙØ«Ø±Ø© Ø§ÙÙØ±Ø§Ø¬Ø¹ ØºÙØ± Ø§ÙÙÙØ§Ø³Ø¨Ø©Ø 5) Ø§ÙÙÙÙÙÙ Ø§ÙØ®Ø§Ø·Ø¦ Ø¹Ù Ø¹ÙÙÙØ© Ø§ÙØ¹Ø¯Ø¯ Ø§ÙØµØÙØ.